The Impact of Cyberattacks on Efficient Operations of CAVs - McManus, Ian; Heaslip, Kevin (Frontiers in Future Transportation, 2022)
The implementation of connected and autonomous vehicles promises increased safety and efficiency by leveraging advances in technology. With this new technology, there could be vulnerabilities that lead to cyberattacks. Without a focus on cybersecurity, vehicles may be attacked, leading to a reduction in the efficiency and safety advantages promised through technological advancement. This research performed an impact analysis on traffic operations of cyberattacks on VANETs. A traffic and communications simulation was created using modeling software that incorporated V2X communication and could model Denial of Service (DoS) and Man in the Middle (MITM) attacks on an urban street network. The number of compromised intersections and attack success rate were manipulated to gain a breadth of results. Each attack’s worst-case scenario resulted in an over 20% increase in delay per vehicle as the attack severity increased. Also, the attacks had a wide variation in delay upon the network, decreasing the travel time reliability and the ability for road users to predict delay on their journey. Overall, understanding the transportation impacts of cyberattacks on VANETs is an important step to developing mitigation and resilient infrastructure.